Whole-genome DNA methylation characteristics in pediatric precursor B cell acute lymphoblastic leukemia (BCP ALL). - Radosław Chaber; Artur Gurgul; Grażyna Wróbel; Olga Haus; Anna Tomoń; Jerzy Kowalczyk; Tomasz Szmatoła; Igor Jasielczuk; Blanka Rybka; Renata Ryczan-Krawczyk; Ewa Duszeńko; Sylwia Stąpor; et al. (PLoS ONE, 2017)
In addition to genetic alterations, epigenetic abnormalities have been shown to underlie the pathogenesis of acute lymphoblastic leukemia (ALL)-the most common pediatric cancer. The purpose of this study was to characterize the whole genome DNA methylation profile in children with precursor B-cell ALL (BCP ALL) and to compare this profile with methylation observed in normal bone marrow samples. Additional efforts were made to correlate the observed methylation patterns with selected clinical features. We assessed DNA methylation from bone marrow samples obtained from 38 children with BCP ALL at the time of diagnosis along with 4 samples of normal bone marrow cells as controls using Infinium MethylationEPIC BeadChip Array. Patients were diagnosed and stratified into prognosis groups according to the BFM ALL IC 2009 protocol. The analysis of differentially methylated sites across the genome as well as promoter methylation profiles allowed clear separation of the leukemic and control samples into two clusters. 86.6% of the promoter-associated differentially methylated sites were hypermethylated in BCP ALL. Seven sites were found to correlate with the BFM ALL IC 2009 high risk group. Amongst these, one was located within the gene body of the MBP gene and another was within the promoter region- PSMF1 gene. Differentially methylated sites that were significantly related with subsets of patients with ETV6-RUNX1 fusion and hyperdiploidy. The analyzed translocations and change of genes' sequence context does not affect methylation and methylation seems not to be a mechanism for the regulation of expression of the resulting fusion genes.